Optimization of Pectinase Production on Solid Substrates by Rhizopus sp. 26R Capable of Raw Cassava Starch Hydrolysis - Lerluck Chitradon; Polson Mahakhan; Vichien Kitpreechavanich; Napha Lotong (Agriculture and Natural Resources, 1992)
Eleven strains of Aspergillus spp. and 3 strains of Rhizopus spp. efficient in raw cassava starch hydrolysis were also found to be good in pectinase activity. Strain selection was performed by using solid substrate fermentation composing of wheat bran and rice husk in a ratio of 18:2. It revealed that Rhizopus sp. 26R gave almost the highest activity in 2 days and remained constant for 4 days. Optimization studies showed that addition of either 1 g raw cassava starch or pectin to a 20 g substrate increased the enzyme activity to 1.7 and 2.4 times, respectively. The highest activity, however, obtained when the strain was grown on substrate containing a mixture of wheat bran, rice bran and rice husk in a ratio of 9:9:2 or 6:12:2 with 58% initial moisture content, pH adjusted to 5.7 and incubation was at 32 degree C. Under these conditions, Rhizopus sp. 26R produced ca. 700 units of enzyme activity per gram of wet weight substrate.